The Effect of Work Motivation and Workload on Employee Performance in Regional Research and Development Agency - Asbi Maulana; M. Risal (Institute of Computer Science (IOCS), 2022)
This study aims to describe and identify the role of work motivation and workload in influencing employee performance. The total population in this study were 35 employees at the Regional Research and Development Agency of Palopo City. Hypothesis testing using multiple linear regression analysis using SPSS application, Y = 4,800 + 0,449X1+0,301X2. Results obtained on Partial testing (t-test) is that the motivation variable has a significant positive effect on employee performance 2,209 and the workload variable has a positive and significant effect on employee performance 1,782. The results of the determination coefficient test show a value of 0.304, meaning that employee performance is influenced by work motivation and workload of 30.4%, while the remaining 69.6% is influenced by other variables. The result of the calculation is that the number F count (7.002) > F table (4.14) so ??that Ho is rejected and Ha is accepted. Partially and simultaneously, motivation and workload have a significant effect on employee performance.